Urgensi Kekerasan di Satuan Pendidikan: Bagaimana Peran Permendikbudristek PPKSP? - Wahyuni, Dela Sri; Asbari, Masduki; Desrifitri, Arum Dalu (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to determine the prevention and control of violence in educational units. Based on or Permendikbukristek PPKSP, this study report uses a descriptive qualitative method by taking notes because the data source was obtained by listening to oral narratives from the Indonesian Ministry of Education and Culture's Smart Character Youtube channel entitled "The Urgency of Preventing and Overcoming Violence in Educational Units" presented by Nadiem Anwar Makarim, B.A., M.B.A. The results of this study explain that the Minister of Education and Culture Regulation explains about. The scope of violence that occurs within the educational unit and outside the location of the educational unit, for example, field trip internships and/or Jamborees as well as violence involving more than one educational unit, the definition and forms of violence are explained in detail to provide clarity about things that are not permitted. Carried out within the education unit, prevention mechanisms that need to be implemented by the education unit, local government and the Ministry of Education and Culture, procedures for handling violence that side with the victim and support the victim's recovery